STUDI FAKTOR PENENTU PENERIMAAN DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA LEMBAGA PERKREDITAN DESA - I Made Suarta; IGA Oka Sudiadnyani (Jurnal Sistem Informasi, 2014)
Abstract This study examines the acceptance of computer-based accounting information systems at the Village Micro Financial Institutions (Lembaga Perkreditan Desa or LPD), by adopting the Technology Acceptance Model (TAM). Modification of the model performed on external factors, because these factors are determined by the LPD’s background as a traditional financial institution owned by indigenous villages. The study uses a non-experimental quantitative approach and ex-post facto research. Data collected by survey method, using a questionnaire. The respondents were selected randomly proportional from employees LPD in Badung regency and Denpasar city. The operational transaction processing, financial and management reporting at LPD is not fully utilizing computer-based accounting information system. Meanwhile, the structural model developed based on the theoretical study is not well supported by empirical data. The total effect of external factors on the actual use of computer-based accounting information systems in the LPD is not significant. Further research is needed, with revise the model and consider additional indicators as part of the external variables in order to provide a comprehensive model.